Optimization and Practice for Partition Pressure Relief of Deep Mining Roadway Using Empty-Hole and Deep-Hole Blasting to Weaken Coal - Baobao Chen; Changyou Liu; Fengfeng Wu (Geofluids)
Rockbursts are among the most harmful dynamic disasters, threatening the personnel safety and mine operation. In order to alleviate stress concentration of roadsides and prevent rockbursts, the large-diameter boreholes and deep-hole blasting are employed for partition pressure relief in the deep mining roadway. Combined with failure behavior and stress distribution of the coal, the multilevel division of risk degree for roadsides stress is determined. Based on the orthogonal test of borehole pressure relief in the general danger partition, the response degree of quantitative indexes to main factors influencing the pressure relief effect is considered. The optimal drilling parameters of 120.0 mm diameter, 20.0 m depth, 1.0 m hole spacing, and 5° elevation angle are obtained, determining the stress boundary of safe pressure relief with boreholes. At higher dangerous stress divisions, the optimized blasting parameters through numerical simulation could be obtained as follows: 15.0 m depth, 1.3 decoupling coefficient, and 2.0 m hole spacing, and meanwhile, a stress relief partition of crisscross cracks with 0.61 m height is formed. The roadsides stress could be well controlled within the safe level. Then, an optimal combination of pressure relief is applied to different stress partition of roadsides, and the effectiveness is validated by field test, which proves remarkably applicable for engineering.